Archaeology at Shiloh Indian mounds, 1899-1999 - Welch, Paul D., 1955- (Book collections on Project MUSE., 2006)
The Shiloh Indian Mounds archaeological site, a National Historic Landmark, is a late prehistoric community within the boundaries of the Shiloh National Military Park on the banks of the Tennessee River, where one of the bloodiest battles of the Civil War was fought in April 1862. Dating between AD 1000 and 1450, the archaeological site includes at least eight mounds and more than 100 houses. It is unique in that the land has never been plowed, so visitors can walk around the area and find the collapsed remains of 800-year-old houses and the 900-meter-long palisade with bastions that protected.